Dual role of α7 nicotinic acetylcholine receptors in the retrosplenial cortex for aversive memory acquisition and retrieval - Pastor, Verónica; Katche, Cynthia (Frontiers in Behavioral Neuroscience, 2024)
In the retrosplenial cortex (RSC), the role of cholinergic modulation via α7 nicotinic receptors and their involvement in memory is unknown. In recent years, the RSC has been shown to deteriorate in the early stages of Alzheimer's disease (AD). Likewise, the cholinergic system has been postulated as one of those responsible for cognitive impairment in patients with AD. Great interest has arisen in the study of α7 nicotinic receptors as more specific targets for the treatment of this disease. For this reason, we aim to study the role of α7 receptors of the RSC in memory processing. We infused a selective α7 receptor antagonist into the anterior part of the RSC (aRSC) to assess its role in different phases of aversive memory processing using an inhibitory avoidance task. We found that α7 nicotinic receptors are involved in memory acquisition and expression, but not in its consolidation. These results identify aRSC α7 nicotinic receptors as key players in aversive memory processing and highlight their significant potential as therapeutic targets for Alzheimer's disease.